Comparison of glyburide and insulin in the management of gestational diabetes: A meta-analysis. - Rongjing Song; Ling Chen; Yue Chen; Xia Si; Yi Liu; Yue Liu; David M Irwin; Wanyu Feng (PLoS ONE)
Objective The aim of this meta-analysis was to determine the efficacy and safety of glyburide as a treatment for gestational diabetes mellitus (GDM) compared to insulin. Methods A meta-analysis was conducted to compare the management of gestational diabetes with glyburide and insulin. Studies fulfilling all of the following inclusion criteria were included in this meta-analysis: subjects were women with gestational diabetes requiring drug treatment; the comparison treatment included glyburide vs insulin; one or more outcomes (maternal or neonatal) should be provided in the individual study; the study design should be a randomized control trial. Exclusion criteria: non-RCT studies; non-human data. PubMed, Embase and CENTRAL databases were searched from inception until 10 October 2016. Results Ten randomized control trials involving 1194 participants met the inclusion criteria and were included. 13 primary outcomes (6 maternal, 7 neonatal) and 26 secondary outcomes (9 maternal, 17 neonatal) were detected and analyzed in this study. Glyburide significantly increased the risk of any neonatal hypoglycemia [risk ratio (RR), 1.89; 95% confidence interval (95%CI), 1.26 to 2.82; p = 0.002]. Sensitivity analysis confirmed robustness of this result [RR, 2.29; 95%CI, 1.49 to 3.54; p = 0.0002]. No differences were observed between the two groups with respect to birth weights [mean difference (MD), 79; 95%CI, -64 to 221.99; p = 0.28] and the risk of macrosomia [RR, 1.69; 95%CI, 0.57 to 5.08; p = 0.35]. Conclusion For women with gestational diabetes, no differences in maternal short term outcomes were observed in those treated with glyburide or insulin. However, the incidence of neonatal hypoglycemia was higher in the glyburide group compared to the insulin group.